A review of carbon–carbon composites for engineering applications. (November 2015) - Su, Jun-ming; Zhou, Shao-jian; Li, Rui-zhen; Xiao, Zhi-chao; Cui, Hong
Abstract : Five kinds of carbon–carbon composites used in aerospace, aircraft, photovoltaics, powder metallurgy and high temperature furnaces are reviewed, whose preforms were fabricated by needle piercing, orthogonal three-direction weaving, radial weaving, axial weaving and puncture. The physical, mechanical, thermal, ablation, and wear properties and service life were compared with corresponding materials from overseas manufacturers. Correlations between the performance, type of preform and carbon matrix, and interfacial bonding state was obtained. These analyses and comparisons can lay a foundation for the construction of a database-sharing platform for C/C composites in engineering applications. Research efforts need to be focused on the fine structure and gradient design of preforms and the optimum combination of different carbon matrices for the improvement of C/C composites. [New Carbon Materials 2015, 30(2): 106–114]